O contributo de Mies van der Rohe para a flexibilidade na Arquitectura Moderna. - Mónica Raquel Azevedo da Silva (2011)
I will start by raising questions about the Dwelling. What new forms exist, which proposals along in history have emerged, which reinterpretations may exist and arise. I understand that new ways will arise spontaneously in this, but others will inevitably arise from the past. A solid past to which today appealed to the answers the present and the future. The form of inhabit is so varied, and all possibilities are different depending on the our needs. There is, therefore, a plurality of responses for each demand for each individual conformation of dwelling. However, something awakened me to the following: time. Over time, the way of living can not be the same: the needs change over time. "Life can change the architecture." (1) So, how can we adapt our needs to the plant, which is rigid, and in $ exible? I seek an answer in flexibility.